1995
DOI: 10.1203/00006450-199503000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cytochrome aa3 Measured by Near-Infrared Spectroscopy Predicts Cerebral Energy Loss in Hypoxic Piglets

Abstract: Near-infrared spectroscopy is a noninvasive monitoring technique that allows quantitative measurement of changes in cerebral oxygenated Hb (HbO,), deoxygenated Hb (Hb), total Hb, and oxidized cytochrome aa, (CytO,). Changes in cerebral Hb oxygenation and CytO, have been measured in human neonates and infants under a variety of conditions. However, the association of these measurements with cerebral high-energy phosphate loss is not known. We studied simultaneous changes in cerebral HbO,, Hb, total Hb, and CytO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 23 publications
(30 reference statements)
6
46
1
Order By: Relevance
“…There is concern that ACytaa3 does not properly reflect changes in brain cell oxygenation, be cause of the use of the wrong algorithms for calculation of its changes [26,34]. Moreover, the normally low-energy requirement of the newborn brain may mask fluctuations in the oxidation-reduction level of the enzyme and effect the reliability of ACytaa3 as a marker of actual changes in oxidation of the enzyme Cytaa3 [35], In this respect, however, it is important to mention the results of a recent study in hypoxic newborn pigs which showed that reduction of Cytaa3, measured by NIRS, predicted indeed cerebral energy loss in these animals [36], Although the value of ACytaa3 as a marker of brain cell oxygenation remains uncertain so far, our results suggest a role for ACytaa3 as a relative measure for cerebral oxi dation. Yager et al [7] showed in newborn dogs major perturbations in the energy status of the brain early after the start of hypother mic circulatory arrest: ATP was preserved only during the first 10 min after the start of circulatory arrest in the parietal cortex, sug gesting alterations in oxidative and energy metabolism thereafter.…”
Section: Discussionmentioning
confidence: 55%
“…There is concern that ACytaa3 does not properly reflect changes in brain cell oxygenation, be cause of the use of the wrong algorithms for calculation of its changes [26,34]. Moreover, the normally low-energy requirement of the newborn brain may mask fluctuations in the oxidation-reduction level of the enzyme and effect the reliability of ACytaa3 as a marker of actual changes in oxidation of the enzyme Cytaa3 [35], In this respect, however, it is important to mention the results of a recent study in hypoxic newborn pigs which showed that reduction of Cytaa3, measured by NIRS, predicted indeed cerebral energy loss in these animals [36], Although the value of ACytaa3 as a marker of brain cell oxygenation remains uncertain so far, our results suggest a role for ACytaa3 as a relative measure for cerebral oxi dation. Yager et al [7] showed in newborn dogs major perturbations in the energy status of the brain early after the start of hypother mic circulatory arrest: ATP was preserved only during the first 10 min after the start of circulatory arrest in the parietal cortex, sug gesting alterations in oxidative and energy metabolism thereafter.…”
Section: Discussionmentioning
confidence: 55%
“…These mediators lead to dysregulation of cerebral vascular tone (Lassen 1964;Meek et al 1999). The association between cerebrovascular dysfunction and cerebral injury has been supported by studies linking CBF abnormalities with proton magnetic resonance spectroscopy markers of cerebral energy failure (Tsuji et al 1995;Winter et al 2009) and adverse neurological outcomes (Meek et al 1999;Pryds et al 1990;Toet et al 2006;Zaramella et al 2007).…”
Section: Discussionmentioning
confidence: 83%
“…More recently, NIRS has emerged as an alternative method to interrogate CBF continuously and noninvasively at the bedside (Edwards et al 1988;Skov et al 1991). While prior studies have linked NIRS measures with outcomes in HIE (Ancora et al 2013;Lemmers et al 2013;Meek et al 1999;Toet et al 2006;van Bel et al 1993;Zaramella et al 2007), few studies have focused on evaluating the relationship between MAP and NIRS as a method to interrogate autoregulation (Howlett et al 2013;Tekes et al 2015). Signs of impaired cerebral pressure autoregulation may precede the presence of unregulated CBF, giving this approach the potential advantage of directing intervention before irreversible injury has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations have previously been shown with cortical impedance , [ATP] (Tsuji et al 1996) and EEG & Tamura 1993). We therefore used our neonatal piglet model ) to perform simultaneous NIRS and magnetic resonance spec-tochrome oxidase IRS C. E. Cooper and R. Springett .…”
Section: (B) Neonatal Hypoxia-ischaemiamentioning
confidence: 99%